Improvements in energy consumption and environmental impact by novel single shot melting process for casting - Salonitis, Konstantinos; Jolly, Mark R.; Zeng, Binxu; Mehrabi, Hamid (Elsevier, 2016)
The CRIMSON (Constrained Rapid Induction Melting Single Shot Up-Casting) method uses a rapid induction furnace to melt just enough metal for a single mould rather than bulk melting used in traditional casting process. The molten metal is then transferred to a computer – controlled platform to complete the counter-gravity up filling. The highly controlled metal flow is pushed into the mould to finish the pouring and solidification. In the present paper the energy saving capability of CRIMSON approach is compared with conventional sand casting process. The paper focuses on the energy and resource efficiency optimization of casting stages through simulation and life cycle assessment analysis simulation for proposing alternative means for the better performance of such processes. It is proven that the CRIMSON process can produce high quality castings with higher energy efficiency and lower environmental impact.
Keywords: Casting; Foundry sector; CRIMSON; Sand casting; LCA; Yield